2014
DOI: 10.1016/j.bbamcr.2014.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically induced restructuring of focal adhesions causes mobilization of vinculin by a vesicular endocytic recycling pathway

Abstract: In epithelial cells, vinculin is enriched in cell adhesion structures but is in equilibrium with a large cytosolic pool. It is accepted that when cells adhere to the extracellular matrix, a part of the soluble cytosolic pool of vinculin is recruited to specialized sites on the plasma membrane called focal adhesions (FAs) by binding to plasma membrane phosphatidylinositol-4,5-bisphosphate (PtdIns(4,5)P2). We have previously shown that bradykinin (BK) induces both a reversible dissipation of vinculin from FAs, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…A proteomic analysis demonstrated the presence of Rab5 and EEA1 within isolated integrin adhesion complexes (27). Furthermore, vinculin, another scaffolding protein has been found to be associated with endosomal vesicles and clathrin-mediated endocytosis (28,29). This is consistent with a study that demonstrated a colocalization between FA and clathrin adaptors (Dab2, AP-1 and numb), which may be found in the plasma membrane and early endosomes (17).…”
Section: Discussionsupporting
confidence: 84%
“…A proteomic analysis demonstrated the presence of Rab5 and EEA1 within isolated integrin adhesion complexes (27). Furthermore, vinculin, another scaffolding protein has been found to be associated with endosomal vesicles and clathrin-mediated endocytosis (28,29). This is consistent with a study that demonstrated a colocalization between FA and clathrin adaptors (Dab2, AP-1 and numb), which may be found in the plasma membrane and early endosomes (17).…”
Section: Discussionsupporting
confidence: 84%
“…79,80 Furthermore, different cell types react differently to biomaterials. [81][82][83] Therefore, it is difficult to draw a conclusive explanation for the different cell behaviour of MC3T3 cells when cultured on pTMSPMA/SiO 2 and I100 disks. The combination of a more hydrophilic, negatively charged surface and the inherent chemistry of pTMSPMA is likely to contribute to the improved cell attachment and spreading.…”
Section: Cell Viabilitymentioning
confidence: 99%
“…Vinculin expression did not show a significant modulation ( Figure 4 D). Given that various stimuli have been shown to induce reversible dissipation of vinculin from focal adhesions and internalization of vinculin into vesicles [ 21 ], we investigated, by immunofluorescence, the distribution of vinculin in VECs. The same ECM substrates that showed low adherence of VECs, namely, collagen I, fibronectin, or vitronectin, were used for plate coating before cultivating VECs and treating cells with high glucose or direct interaction with monocytes.…”
Section: Resultsmentioning
confidence: 99%